2015
DOI: 10.1017/s1041610215000423
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DEM-DISC, customized e-advice on health and social support services for informal carers and case managers of people with dementia; a cluster randomized trial

Abstract: This study demonstrates that using DEM-DISC had a positive effect on the sense of competence and experienced (met) needs of informal carers. This shows the importance of user-friendly ICT solutions to assist carers in finding appropriate care services tailored to their specific situation and needs. For further implementation of DEM-DISC methods to keep the information updated is of great importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…Examples of effective interventions for the informal and formal caregivers are: psychoeducational programmes, including online skills training (Hattink et al, 2015); staff awareness training (Clare et al, 2013) and cooperative communication interventions between staff and family caregivers as partners in caregiving (Robinson et al, 2007); brief, individually tailored behavioural interventions designed for caregivers to reduce people with dementia's reluctance to attend day care services (Nogales-Gonz alez, Losada-Baltar, M arquez-Gonz alez, & Zarit, 2014); and a web-based tool to support carers in finding services they need (Van Mierlo et al, 2015).…”
Section: Interventionsmentioning
confidence: 99%
“…Examples of effective interventions for the informal and formal caregivers are: psychoeducational programmes, including online skills training (Hattink et al, 2015); staff awareness training (Clare et al, 2013) and cooperative communication interventions between staff and family caregivers as partners in caregiving (Robinson et al, 2007); brief, individually tailored behavioural interventions designed for caregivers to reduce people with dementia's reluctance to attend day care services (Nogales-Gonz alez, Losada-Baltar, M arquez-Gonz alez, & Zarit, 2014); and a web-based tool to support carers in finding services they need (Van Mierlo et al, 2015).…”
Section: Interventionsmentioning
confidence: 99%
“…While one of the studies reported positive results [84], the other one found positive results on physical functioning, but reported negative effects on emotional performance as a study result [85].There is only one study -an RCT -that targets the support of informal caregivers by evaluating a personalised tool to support carers of people with dementias. The study does not report any positive effects on care receivers, but documents an increased sense of competence in caregivers after 12 months of using the tool [86]. A qualitative study on a personal assistant for dementia identi es positive effects on patients, but no effects on the burden on the family [87].…”
Section: Speci C Software/appsmentioning
confidence: 79%
“… Primary (PwC): Cognitive functioning (MMSE; DRS2); everyday activities, self-care and personality change (BDRS); Clinical Dementia Rating Scale; memory and behaviour (RMBPC); Depression (GDS); Functional disability (BI); daily living (LADL); comorbidity (CCI) Follow-up: 3 & 6 mths Significant improvement in QoL of caregivers in intervention participants, with some reduction in burden and distress. Training in program Confidence and awareness of health, provided dementia information Van der Roest et al 2009 [ 24 ] NRCT Netherlands Sample: recruited: 28 Consent rate: NR Setting: Amsterdam Diagnostic group: Caregivers and people with dementia Inclusion criteria: general: ≥4 h per/week caring for community-dwelling dementia patient; to be in experimental: care recipient lives in Amsterdam district; familiar with computers and the internet Exclusion criteria: NR Intervention: internet-based: tailored; information; resources; advice Control group: Usual care Primary: Needs assessment (CANE); burden (SSCQ); self-efficacy (PMS) Secondary: QoL (QoL-AD); knowledge about care and welfare Follow-up: 2 mths Intervention participants reported more met and less unmet needs, and higher competence Intervention was easy to learn and relatively user friendly Intervention used program 5.14 times Mean session duration: 14:36 mins Van Mierlo et al 2015 [ 25 ] RCT The Netherlands Sample: recruited: 73; analysed T1: 64; analysed T2: 49 Consent rate: 89% Setting: Several regions of the Netherlands (Amsterdam Zuidoost, Amsterdam Nieuw-West, regions of Lelystad and Amstelveen) Inclusion criteria: Informal caregivers of people with Dementia; computer with internet capabilities; knows how to use computer Exclusion criteria: Not able to understand/read Dutch; anticipated nursing home admission ≤6mths Intervention: internet-based: available for 1 yr.; case manager and carer access tailored; advice Control group: Usual care Primary: Needs of people with Dementia (CANE) Secondary: Competence (SSCQ); QoL (EQ5D + c); stress (NPI) Follow-up: 6 mths; 12 mths Increased competence in intervention participants at 12 mths. Active users in the intervention group reported more met needs than controls at 6 mths.…”
Section: Resultsmentioning
confidence: 99%
“…However, utilisation was variable. Two studies reported a dose-response relationship, with active users reporting greater benefits [ 23 , 25 ]. Three studies incorporated online technical support to encourage engagement [ 22 , 23 , 27 ], while others used automated reminders [ 23 , 28 ]; follow-up calls [ 27 ]; health professional contact via chat functions or forums [ 25 ]; and financial incentives [ 23 , 29 ].…”
Section: Resultsmentioning
confidence: 99%